Answer:
h(x - 1) = -5x - 2
General Formulas and Concepts:
<u>Pre-Algebra</u>
<u>Algebra I</u>
Terms/Coefficients
Functions
Step-by-step explanation:
<u>Step 1: Define</u>
<em>Identify</em>
h(x) = -5x - 7
<u>Step 2: Find</u>
- Substitute in <em>x </em>[Function h(x)]: h(x - 1) = -5(x - 1) - 7
- [Distributive Property] Distribute -5: h(x - 1) = -5x + 5 - 7
- Combine like terms: h(x - 1) = -5x - 2
Answer:
(0,0)
Step-by-step explanation:
For this, you need to use the midpoint formula.
(-3) + 3 2 + (-2)
-------------- , ----------------
2 2
This leads to:
-3 + 3 = 0 -> 0/2
x = 0
3 + (-3) = 0 -> 0/2
The answer is:
(0, 0)
x =
or x = - ![\frac{4}{3}](https://tex.z-dn.net/?f=%5Cfrac%7B4%7D%7B3%7D)
consider the factors of the product 6 × - 4 = - 24 which sum to the coefficient of the x- term ( + 5)
the factors are + 8 and - 3 ( split the middle term using these factors
6x² - 3x + 8x - 4 = 0 ( factor by grouping )
3x(2x - 1) + 4(2x - 1 ) ( take out common factor of (2x - 1) )
= (2x - 1)(3x + 4) = 0
equate each factor to zero and solve for x
2x - 1 = 0 ⇒ x = ![\frac{1}{2}](https://tex.z-dn.net/?f=%5Cfrac%7B1%7D%7B2%7D)
3x + 4 = 0 ⇒ x = - ![\frac{4}{3}](https://tex.z-dn.net/?f=%5Cfrac%7B4%7D%7B3%7D)
Answer:
false
Step-by-step explanation:
if you do 4/4 it is 1 which is odd